Perineural invasion and the “cold” tumor microenvironment in pancreatic cancer: mechanisms of crosstalk and therapeutic opportunities - Xu, Jianbiao; Yao, Hong; Wang, Junfeng; Jin, Yun; Chang, Wei; Li, Lanjiang; Zou, Lei (Frontiers in Immunology, 2025)
Pancreatic ductal adenocarcinoma (PDAC) remains a devastating malignancy characterized by profound lethality, aggressive local invasion, dismal prognosis, and significant resistance to existing therapies. Two critical biological features underpin the challenges in treating PDAC: extensive perineural invasion (PNI), the process by which cancer cells infiltrate and migrate along nerves, and a profoundly immunosuppressive, or “cold,” tumor microenvironment (TME). PNI is not only a primary route for local tumor dissemination and recurrence but also a major contributor to the severe pain often experienced by patients. Concurrently, the PDAC TME is typified by a dense desmoplastic stroma, hypoxia, and an abundance of immunosuppressive cells—including cancer-associated fibroblasts (CAFs), tumor-associated macrophages (TAMs), myeloid-derived suppressor cells (MDSCs), and regulatory T cells (Tregs)—while lacking sufficient infiltration of effector T cells, rendering it largely unresponsive to immunotherapies like checkpoint inhibitors. Although historically studied as separate entities, accumulating evidence reveals a deep-seated and complex bidirectional crosstalk between the neural components involved in PNI and the immune and stromal cells constituting the TME. Key cellular mediators, such as CAFs and TAMs, and shared signaling pathways, including the CXCL12/CXCR4 axis, TGF-β signaling, and neurotrophin pathways (e.g., NGF/TrkA), appear to act as critical nodes, coordinating the progression of PNI while simultaneously shaping and maintaining the immunosuppressive TME. This review synthesizes the current understanding of these intricate neuro-immune interactions in PDAC. We delineate the molecular and cellular mechanisms governing this crosstalk and explore how targeting these shared regulatory networks presents novel therapeutic opportunities, potentially disrupting PNI while concurrently “heating” the cold TME to overcome immunotherapy resistance. Elucidating this interplay is crucial not only for a deeper comprehension of PDAC’s invasive and metastatic mechanisms but also for uncovering new therapeutic vulnerabilities to improve patient outcomes.